Mini-companies as "greenhouses" of economic competence: A longitudinal study of "Young Enterprise Switzerland" - Carsten Quesel; Guido Moeser; Susanne Burren (Journal of Global Entrepreneurship Research, 2017)
The paper investigates how Swiss students on the higher secondary level evaluate their participation in mini-companies. Theoretically, the study draws on the concept of project-based learning (PBL). Data was collected in the first and the last stages of the projects and are analyzed by structural equation modelling (SEM). The analysis shows that the students display relatively stable attitudes regarding the development of specific business skills and regarding the impact of participation on the general development of competencies.
Keywords: 650; Entrepreneurship education; Mini-companies; Project-based learning